The role of guilt and shame-proneness and externalization of blame as risk factors for inflammatory bowel disease - Papacosta, Lolita; Argyrides, Marios; Anastasiades, Elly; Petkari, Eleni (North American Journal of Psychology, 2022)
Various psychological factors have been found to be associated with the onset of Inflammatory Bowel Disease (IBD). Despite this, there remains a lack of acceptance for a biopsychosocial model of intervention, specifically targeted to the prevention and treatment of IBD. The aim of this study was to assess the predictive relationships between guilt-proneness, shame-proneness, externalization of blame and IBD. The study employed a quasi-experimental study design. The Short-Form-Test-of-Self-Conscious-Affect (TOSCA-3) was administered to 128 IBD patients and 129 controls without IBD. Independent t-tests revealed significant differences in shame-proneness and guilt-proneness between IBD patients and controls. In addition, a binary logistic regression analysis revealed that the odds of having IBD were significantly higher for individuals with high shame-proneness, high guilt-proneness and low levels of externalization of blame. The findings highlight the significance of guilt and shame-proneness as risk factors for IBD, and of externalization of blame as a protective factor, through the reduction of shame-proneness. Psychological interventions aimed at the reduction of guilt and shame-proneness could potentially attenuate illness expression of IBD.
Keywords: guilt; inflammatory bowel disease; psychological adaptation; self-conscious emotions; shame; Scopus